Políticas de comunidade nos terrenos da educação - Gotardo, Suzana Maria (2011)
The present study, conducted in a school of federal network of professional education, science and technology in the state of Espirito Santo and linked to agricultural training offered to investigate what we call the politics of community: the forms that are called community, field of forces that produce them, their uses and meanings. We look for with it investigate how the object built community historically has been operated in the realms of education, place objects and school community in the crucible of history, as well as naturalization in this school-community expression, analyze the practices that produce under the name of the community and the effects of reality that these practices produce, affirm a concept of community that put up the lived experiences in this particular school. Throughout the text, we try to show how much these policies of community are diverse, operating both catches, segmentations and individualized movements, the practice of solidarity, collective and otherness, which seek to affirm. It is a foray into that passes for community-forms crystallized as well as the production of another modes of community possible/experienced in the course of this research.